Surface mesh quality improvement by weighted inscribed circle method. (October 2019) - Peng, Wei; Ji, Weixi
Highlights: Mesh improvement by combination of node classification and node relocation. The normal tensor voting theory is used to classify all surface nodes. Optimize the node position by weighted average method of the inscribed circles. The piecewise linear approximation method is adopted to approach the input mesh. Abstract: Surface mesh quality is one of key factors in finite element applications, since it affects the accuracy and efficiency of finite element simulation and influences the quality of subsequently generated solid mesh. In this paper, we proposed a novel surface mesh smoothing algorithm which aims to produce a more regular mesh from a given input mesh, while accurately preserving its sharp features such as edges and corners. The mesh quality is improved by a combination of surface node classification and node relocation, while the new position of the vertex is obtained by weighted average of the centers of inscribed circles of the surrounding polygon, and projecting the averaged position to lie in space near the input surface mesh. The procedure above is repeated until the maximal change of mesh quality is less than a pre-defined threshold. Finally, several experimental results are presented to demonstrate the effectiveness and practicability of our method.